Energy Efficiency and Renewable Energy Through Nanotechnology - Zang, Ling (Green Energy and Technology, 2011)
Reflecting the rapid growth of nanotechnology research and the potential impact of the growing energy crisis, Energy Efficiency and Renewable Energy Through Nanotechnology provides comprehensive coverage of cutting-edge research in the energy-related fields of nanoscience and nanotechnology, which aim to improve energy efficiency and the generation of renewable energy. Energy Efficiency and Renewable Energy Through Nanotechnology tightly correlates nanotechnology with energy issues in a general, comprehensive way that makes it not only suitable as a desk reference for research, but also as a knowledge resource for the non-expert general public. Readers will find Energy Efficiency and Renewable Energy Through Nanotechnology useful in a variety of ways, ranging from the creation of energy policy, to energy research development, and to education in nanotechnology and its application to energy-related problems. It can also be used as a primary or supplementary textbook for energy-related courses for advanced undergraduate and graduate students.